Honours versus money the economics of awards - Frey, Bruno S.; Gallus, Jana (Oxford University Press, 2017)
Honours fulfil one of the most fundamental desires of human beings, namely, to be recognised and held in esteem by others. There are thousands of awards in all areas of society: the state, arts and media, sports, religion, the voluntary sector, academia, and business. Awards are well visible, can raise the recipients' intrinsic motivation and creativity, and establish a bond of loyalty to the giver. They have distinct advantages over money and other rewards. Presenting empirical evidence using modern statistical techniques, this book argues that awards can significantly raise performance in different contexts even if they are purely symbolic, recommending how this can be used in practice.